Elbasvir/grazoprevir in Asia‐Pacific/Russian participants with chronic hepatitis C virus genotype 1, 4, or 6 infection. Issue 5 (4th April 2018) - George, Jacob; Burnevich, Eduard; Sheen, I‐Shyan; Heo, Jeong; Kinh, Nguyen Van; Tanwandee, Tawesak; Cheng, Pin‐Nan; Kim, Do Young; Tak, Won Young; Kizhlo, Svetlana; Zhdanov, Konstantin; Isakov, Vasily; et al.
Abstract : C‐CORAL was the first phase 3 study to evaluate the efficacy and safety of EBR/GZR in participants with HCV infection from the Asia‐Pacific region and Russia. SVR at 12 weeks was achieved by 93% of participants overall, with notably high rates in those with HCV GT1b infection (98.9%) and low rates in those with GT6 infection (62.9%). Abstract : The prevalence of hepatitis C virus (HCV) infection in Asian countries is high. This study assessed the efficacy and safety of elbasvir/grazoprevir (EBR/GZR) in participants with HCV infection from Asia‐Pacific countries and Russia. In this phase 3, randomized, placebo‐controlled, double‐blind study, treatment‐naive participants with HCV genotype (GT) 1, 4, or 6 infection were randomized to EBR 50 mg/GZR 100 mg (immediate‐treatment group [ITG]) or placebo (deferred‐treatment group [DTG]) once daily for 12 weeks (Protocol PN‐5172‐067, NCT02251990). The primary efficacy variable was a nonrandomized comparison of sustained virologic response at 12 weeks after the end of therapy (SVR12) for the ITG with a historical control. The primary safety outcome was a randomized comparison between the ITG and DTG. Three hundred thirty‐seven participants were randomized to the ITG (n = 251) or DTG (n = 86); 199 (59.2%) participants were Asian, and 250 (74.4%) had HCV GT1b infection. Overall, 232/250 (92.8%) participants in the ITG achieved SVR12 (97.5% confidence interval, 89.1, 96.5). Of the 18 participants who failed to attain SVR12, 1 was lost to follow‐up and 17 had virologic failure, 13 of whom had HCV GT6 infection. The incidence of adverse events was similar between participants receiving EBR/GZR and placebo (50.8% versus 51.2%; difference, −0.3%; 95% confidence interval, −12.3, 11.9). Conclusion: EBR/GZR for 12 weeks provides an effective and well‐tolerated regimen for chronic HCV GT1 infection in treatment‐naive people from Asia‐Pacific countries and Russia, particularly for the large population with GT1b infection. EBR/GZR is not recommended for the treatment of individuals with HCV GT6 infection. ( Hepatology Communications 2018;2:595‐606)